What's eating us : women, food, and the epidemic of body anxiety - Kazdin, Cole (New York : St. Martin's Essentials, 2023)
"Blending personal narrative and investigative reporting, journalist Cole Kazdin reveals that disordered eating is an epidemic crisis killing millions of women. Women of all ages struggle with disordered eating, preoccupation with food, and body anxiety. Interviewing women across the country as well as the world's most renowned researchers, she discovered that most people with eating disorders never receive treatment. Kazdin takes us to the doorstep of the diet industry and research community, exposing the flawed systems that claim to be helping us, and revealing disordered eating for the crisis that it is: a mental illness with the second highest mortality rate (after opioid-related deaths) that no one wants to talk about."--
"Fixing our messed-up relationship with what we eat and how we look" -- Cover
Includes bibliographical references (pages 231-248).
Keywords: Eating disorders in women -- United States -- Popular works; Body image in women -- United States -- Popular works; Women -- Mental health -- United States -- Popular works; Kazdin, Cole -- Mental health; Self-help publications